2013
DOI: 10.3233/ch-2012-1564
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume does not seem to relate to thrombosis or posterior uveitis in Behçet's disease

Abstract: Behçet's disease (BD) is a chronic inflammatory disorder in which thrombosis and posterior ocular involvement occur in about 30% of patients, whose ethiology is unknown. It has not been established whether mean platelet volume (MPV), a marker of platelet activation, is involved in the pathogenesis of thrombotic events and posterior uveitis in these patients. We aimed to analyze whether there are differences in MPV in BD patients when compared with controls and its relation with the presence of thrombosis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
1
21
6
2
Order By: Relevance
“…In the present study, MPV was significantly lower in patients with BD compared to controls. This is at variance with some previous reports, in which MPV was elevated in patients with BD compared to healthy controls . However, lower MPV has also been reported in patients with BD .…”
Section: Discussioncontrasting
confidence: 88%
“…In the present study, MPV was significantly lower in patients with BD compared to controls. This is at variance with some previous reports, in which MPV was elevated in patients with BD compared to healthy controls . However, lower MPV has also been reported in patients with BD .…”
Section: Discussioncontrasting
confidence: 88%
“…Three of these were excluded because they were duplicate studies. Thus, 14 articles met the inclusion criteria (Table , Figure ). Eleven studies evaluated MPV, seven studies NLR, three studies adinopectin levels, and three studies PLR levels in the BD and control groups (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Behçet’s disease can be classified as active and inactive diseases based on disease activity, and thrombosis occurs often in BD. Studies on MPV, NLR, and PLR in patients with BD in comparison with those in healthy controls, on the indices between active and inactive diseases, and between BD with and without thrombosis have reported controversial results . We performed the present meta‐analysis to overcome the limitations of individual studies and resolve inconsistencies .…”
Section: Introductionmentioning
confidence: 99%
“…15 There are only a few studies that MPV levels have been investigated in Behc ßet's disease. 20,36,37 Previous studies was shown that an increase in MPV may indicate the presence of venous thrombosis, but MPV is an inappropriate marker of activity in BD. 20 We concluded that the MPV levels may be used as a cheap and feasible diagnostic marker in patients with BD in previous study.…”
Section: Discussionmentioning
confidence: 99%